PENGEMBANGAN BAHAN AJAR BERBASIS TUNJUK AJAR MELAYU DI SEKOLAH DASAR - Aini, Nurul; Eddy Noviana; Otang Kurniaman (Jurnal Ilmiah Aquinas, 2022)
This study aims to develop teaching materials based on Malay teaching and learning in elementary schools for fourth-grade elementary school students. The type of writing is Research and development using a 4D development model. The results obtained that teaching materials based on Malay teaching and learning are very valid and very practical so that they are "very feasible" to be used in learning. The validation results from media experts obtained an average score of 93.75% in the "Very Valid" category. The assessment of the material expert validators obtained an average score of 97.91% with the "Very Valid" category. Furthermore, the class teacher validator with the validation results showed an average score of 88.02% with the "Very Valid" category. Assessment of research products in a limited trial using the practicality of teachers and students. The results of the average score of teacher practicality are 88.09% in the very practical category. Then the results of the practicality of students obtained an average score of 87.36% with a very practical category. Keywords : Development, teaching material, Malay Teaching and Learning